2011
DOI: 10.1007/s12098-011-0374-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Arrest Caused by Craniometaphyseal Dysplasia

Abstract: Craniometaphyseal dysplasia is a rare congenital disorder that can cause craniofacial skeleton and tubular bone anomalies. A 7-month-old girl, with congenital facial palsy, mouth breathing, and nasal obstruction, was brought to the hospital because she suffered sudden cardiopulmonary arrest. Computed tomography showed bony narrowing of the choanae. The diagnosis was cardiopulmonary arrest triggered by asphyxia caused by severe choanal stenosis. She showed hypoxic encephalopathy and underwent a tracheotomy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The diagnosis of CMD was made based on the clinical expression (hypertelorism, frontonasal bossing, facial nerve palsy and bony choanal stenosis) and radiographs of the cranial and long bones (Fig. a–c) …”
Section: Ankh Mutations In Craniometaphyseal Dysplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of CMD was made based on the clinical expression (hypertelorism, frontonasal bossing, facial nerve palsy and bony choanal stenosis) and radiographs of the cranial and long bones (Fig. a–c) …”
Section: Ankh Mutations In Craniometaphyseal Dysplasiamentioning
confidence: 99%
“…1a-c). 4 To identify the ANKH mutation in this patient, we performed gene analysis using a blood sample. The DNA extracted from white blood cells was polymerase chain reaction (PCR) amplified and sequenced for all 12 exons of the ANKH gene.…”
mentioning
confidence: 99%
“…Elevation of serum alkaline phosphatase activity has been noted in some cases of CMD ( Cheung et al, 1997 ; Chida et al, 2011 ; Dutra et al, 2012 ; Fanconi et al, 1988 ; Key Jr et al, 1988 ; Richards et al, 1996 ; Sheppard et al, 2003 ; Wu et al, 2016 ; Wu et al, 2021 ; Yamamoto et al, 1993 ). Less frequently, elevations in circulating PTH, hypocalcemia ( Fanconi et al, 1988 ; Sheppard et al, 2003 ), and hypophosphatemia ( Dutra et al, 2012 ; Fanconi et al, 1988 ; Wu et al, 2016 ) have been observed, with concomitant radiographic findings of rickets ( Fanconi et al, 1988 ; Wu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%